(In)Visibility And Representation: Social Justice In Recent Chadian Documentary Films. Issue 3 (2nd September 2017) - Crosta, Suzanne
ABSTRACT: This essay examines how Chadian filmmakers Mahamat-Saleh Haroun and Moubarack Idriss Nour revisit and, at times, re-enact history to provide voice and perspective to key moments in Chadian history. Moubarack Idriss Nour's feature documentary, Le Tchad entre histoire et espoir (2014) and Mahamat-Saleh Haroun's Hissein Habré: Une tragédie tchadienne (2016) are both set against the backdrop of Chad's tumultuous history and its legacies for future generations. Nour provides a historical framework and uses colonial footage and archives, anthropological and historical sources, television interviews, and newscasts to celebrate the achievements of Chadian's current President Idriss Déby Itno. Haroun, on the other hand, revisits critically the cult figure of yesteryear, Hissène Habré, and the legacies of his regime: human rights abuses, including sexual slavery, torture, and mass political killings. Both documentary films include archival research, testimonial accounts of repression, torture, arbitrary arrests, and incarceration. However, the ways in which they conceive and structure their narratives and represent Chadian history, its political leaders, and its spokespersons differ diametrically in their respective documentaries. This essay will compare and contrast the ways in which both filmmakers use the documentary genre and its potential, either to create national heroes and/or critique the culture of violence that has permeated the social fabric of the country. As they represent Chad on screen, Haroun and Nour both focus on the country's violent past but differ in their representation of their homeland, its leaders and their respective visions, and the exploration of the "affective forces" of violence (Abel, 2008) as a necessary step in their cinematic expression to achieve their vision of rebuilding the country and ensuring its sustainable future.